Promoting cooperation through fast response to defection in spatial games. (18th October 2016) - Wang, Xu-Wen; Jiang, Luo-Luo; Nie, Sen; Chen, Shi-Ming; Wang, Bing-Hong
Abstract: Recent experimental research has revealed that the cooperation in dynamic social networks, has significant scope for enhancement because individuals in a social system break the links with defective neighbours. To investigate how the length of defection tolerance affects the cooperation of prisoner's dilemma game in dynamic ring networks, we study evolution of breaking and rewiring operations for social interaction as a response to the defection strategy. Defection tolerance is measured in terms of the time length that an individual tolerates a defector who continuously adopts the defective strategy. The results show that the dynamic nature of human social networks plays an essential role in promoting cooperation. Interestingly, there exists a critical value of the temptation to defect, below which the system is entirely dominated by cooperators, and a lower value of defection tolerance induces a larger threshold of temptation.